The Analysis of The Role of Instant Coffee Price and Quality in Consumer Preference and Purchasing Decision, in Malang, Using Partial Least Square Method - Imam Santoso (Wacana Journal of Social and Humanity Studies, 2017)
Consuming instant coffee has become a culture in various major cities. This can be seen from the greatly increasing numbers of coffee shops as well as coffee drinkers drinking outside their homes. This research is to analyze the role of instant coffee price and quality in consumer preference and purchasing decision. The respondents are 99 out of intendended 100 individuals. Data analysis method used in the research is Partial Least Square (PLS). The Mathematical model formed is Y2 = 0.256 X1 + X2 + 0.719 0.117 Y1. This research shows that the price of instant coffee has influence on consumer preference, however the quality of instant coffee has no significant influence on their preference. Furthermore consumer preference has significant influence in the decision to purchase instant coffee.